Strengthening Participatory Civic Skills of Gen Z in the Digital Era: Innovation in Civic Education - Lisa Retnasari; Aim Abdulkarim; Dadang Sundawa; Prayoga Bestari; Anif Istianah; Suyitno; Ella Kusuma Wardani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study analyzes the strengthening of participatory citizenship skills among Generation Z students in the digital age, with a particular focus on their abilities to engage with public issues, monitor policies, and influence political processes. Using a qualitative approach with 150 participants, data were collected through open-ended questionnaire-based interviews and analyzed using thematic techniques. The research findings indicate that although students demonstrate advanced discursive skills and actively engage in online discussions, their participatory practices exhibit a spectrum of sophistication ranging from basic digital deliberation to more strategic forms of collaboration, such as advocacy, investigation, and documentation. However, these skills often face significant internal and external barriers, including public apathy, misinformation, and unsupportive socio-political practices. The study underscores the urgent need for innovative citizenship education that embraces experiential learning, digital collaboration, and project-based approaches that are adaptive to the characteristics of Generation Z. Recommendations The findings of this study make an important contribution to education because they offer ways to shape responsible citizens through digital integration, participatory pedagogy, and critical digital literacy.